PENGARUH LINGKUNGAN KERJA DAN BUDAYA KERJA TERHADAP MOTIVASI KERJA KARYAWAN PT KENCANA LESTARI LOGISTIK CABANG BINJAI - Adriyan Ramadhan; Rosniwati Br. Bangun; Khamo Waruwu; Mella Yunita (CV Putra Publisher, 2022)
This study aims to determine the effect of the Work Environment and Work Culture on Employee Work Motivation at PT Kencana Lestari Logistik Binjai Branch and carried out at PT Kencana Lestari Logistik Binjai Branch, where the total population and sample are 110 people. The research instrument is a questionnaire with a Likert scale model. Requirements test was conducted to test normality, multicollinearity, heteroscedasticity. The data analysis technique is multiple regression, Partial Test 1 Work Environment variable with a significant level of 0.000 <0.05 at the specified significant level, it can be concluded that the Work Environment variable has an influence on Work Motivation, then Partial Test 2 Work Culture variables at a significant level of 0.002> 0.05 at the specified significant level, it can be concluded that the Work Culture variable has an influence on Work Motivation, while the Anova F Test (simultaneous) with a significance level of 0.000. Where the significant level of F count 0.000 <0.05 indicates that the Work Environment and Work Culture simultaneously have a positive and significant effect on the affected variable, namely Work Motivation. While the percentage of the influence of the independent variable on the dependent variable with the value of R2 (Coefficient of Determination) the result is 39.0%, it is stated that the Work Environment and Work Culture can affect Work Motivation by 39%, and the remaining 61% can be influenced by unknown variables.